Pemanfaatan Brangkasan Tanaman Kaya Nitrogen Sebagai Campuran Media Dua Jenis Jamur Tiram (Pleurotus ostreatus dan Pleurotus flabellatus) - Luxgiyanto Ian; Agus Sugianto; Anis Sholihah (AGRONISMA, 2019)
This research was aimed to know the growth and production of White Oyster Mushrooms and Red Oyster mushrooms in a mixture of varied substrates as well as the value of R/C ratio analysis of this farming business. This research was conducted in home mushroom of Agricultural Faculty of Malang Islamic University in September 2017 until January 2018. Randomized completed factorial with two factors was used. The first factor was type of mushroom (J) consists of J1 (white Oyster Mushrooms) and J2 (Red Oyster Mushrooms). The second factor was variations of substrate mixture (C) composed of C0 (0%), C1 (25%), C2 (50%), and C3 (75%), C4 (100%). The result showed that growth and production of white Oyster Mushrooms and Red Oyster Mushrooms, best production at the treatment respectively are average 319.74 g/bag-white Oyster Mushrooms and log 277.37 g/bag-Red Oyster mushrooms on logs.The dose is a measure of a good substrak mix used as a medium the mushroom is on mixed variable by using a dose of 25% substrak the first time contaminated, the appearance of the body of the fruit body, the number of HSI 24.00 fruit fruit 12.45/bag-logs, diameter hood the body of the fruit length 9.07 centimeters, cm, weighs 4.23 sprigs fresh fruit bodies that weigh a total of 338.56 g/bag-log and biological efficiency of 25.58%. The highest average value in the R/C the highest ratio of mixed media media treatment afforded by the highest contaminated C1 (mixed media contamination 25%) amounting to Rp. 5,445,555 the same as the results of treatment of C0 (0%) contaminated media mix